2019
DOI: 10.1002/pts.2436
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the material elongation in the deep drawing of paperboard

Abstract: In this paper, deep‐drawn paperboard cups are characterized in terms of their elongation along the cup wall. For this purpose, a method for the non‐destructive determination of the elongation was developed and tested. Using the presented method, a parameter study of the process parameters blank holder force, forming temperature, material moisture content, drawing velocity, and clearance ratio was performed. The influence of the process parameters on the cup wall elongation was determined by statistical design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…The authors conclude that because of the three-dimensional forming process, multiaxial loads occur, and the uniaxial tensile test is not sufficiently describing the forming behaviour of the material. Hofmann et al (2019) observed similar behaviour, when at a deep drawing process in high moisture conditions the measured elongation of the cup wall exceeded the elongation at break from the uniaxial tensile test. In that case, they suggested material displacement and multiaxial stress conditions as an explanation.…”
Section: Fixed Blank Press Formingsupporting
confidence: 57%
“…The authors conclude that because of the three-dimensional forming process, multiaxial loads occur, and the uniaxial tensile test is not sufficiently describing the forming behaviour of the material. Hofmann et al (2019) observed similar behaviour, when at a deep drawing process in high moisture conditions the measured elongation of the cup wall exceeded the elongation at break from the uniaxial tensile test. In that case, they suggested material displacement and multiaxial stress conditions as an explanation.…”
Section: Fixed Blank Press Formingsupporting
confidence: 57%
“…The measured force-elongation curves for all test specimen are added in appendix 2, Figs. 24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41. In Fig.…”
Section: Results Of the Materials Testsmentioning
confidence: 97%
“…if the tensile force varies over a winding, the paper tends to shift slightly under the influence of vibration [40,41], so that the tensile force becomes constant between the starting point and the end point of the strip of paper attached to the base panel. In concrete terms, this means that the average tensile force rather than the instantaneous tensile force needs to be regulated during winding to the extent that the instanta- the stiffness of paper is significantly higher than that of stretch film: for the same weight per surface area, the force required for an equally small extension is a factor of 5 to 10 higher (confirmed by the results of this research presented under paragraph 4.4, more specifically the stretch film (SF) curve in figures 6 and 7 below) with paper than with plastic stretch film or, to put it another way: the strip required for the same tensile force is much narrower with paper than with plastic stretch film.…”
mentioning
confidence: 99%
“…The presence of moisture in paper material can make it softer and improve its formability as the greater its moisture content, the weaker the fibre bonds, and so the paper has a lower elastic modulus and tensile strength, making it easier to stretch and form. 2,33 Consequently, to better understand the performance of paperboard materials in thermoforming, the changes in moisture content during the forming were investigated for the specified forming conditions (110 C forming/heating temperature, 3 s forming/heating time and vacuum plus 1 bar forming pressure). The moisture content of the material was measured immediately before forming from the material roll and directly after forming from the formed sample.…”
Section: Densitymentioning
confidence: 99%